ANALISIS PENGARUH SISTEM PEMBAYARAN TERHADAP MAKROEKONOMI - Pramudita, Adithya Kurnia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The payment system plays an important role in the circulation of funds throughout theeconomy. In fact, the size of the economic progress of a country is often identified with the progress of the payment system infrastructure. Therefore, the payment system is a social infrastructure that supports all economic activities, including commercial activities and financial transactions. A payment system safe and efficient is an important mechanism that make up the network function of financial markets and financial systems.Particularly in monetary stability, the stability of the payment system is essential to ensure the smooth non-cash payment transactions carried out by the public and business, as well as to support the stability of the financial system and the implementation of monetary policy. The payment system located in Indonesia, was organized by Bank Indonesia, which is the Real Time Gross Settlement (RTGS). This system is an estuary of the settlement of financial transactions in Indonesia and classified in Systemically Important Payment System. Additionally in accordance with the sole objective of Bank Indonesia is to achieve and maintain rupiah stability.For that, the greater the volume and the nominal value of transactions RTGS may be able to identify the growing economic activities undertaken by the community. The payment system can also assist in making or create a policy with the values or the results of statistical analysis of the payment system. Nevertheless, given its important role in the infrastructure of the financial system, the payment system is also closely related to the financial system and monetary system in Indonesia.One legitimate non-cash payment instruments in Indonesia, namely by means of payment cards (APMK). Therefore, it is possible that the increased use of payment cards (APMK) in lieu of currency which will push inflation in Indonesia..Keywords: Payment System, Macroeconomic, Affect to Macroeconomics.